2013
DOI: 10.1177/1753425913507488
|View full text |Cite
|
Sign up to set email alerts
|

Diminazene aceturate (Berenil) modulates LPS induced pro-inflammatory cytokine production by inhibiting phosphorylation of MAPKs and STAT proteins

Abstract: Although diminazene aceturate (Berenil) is widely used as a trypanolytic agent in livestock, its mechanisms of action remain poorly understood. We previously showed that Berenil treatment suppresses pro-inflammatory cytokine production by splenic and liver macrophages leading to a concomitant reduction in serum cytokine levels in mice infected with Trypanosoma congolense or challenged with LPS. Here, we investigated the molecular mechanisms through which Berenil alters pro-inflammatory cytokine production by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 66 publications
3
33
1
Order By: Relevance
“…The study also showed that DIZE downregulated the phosphorylation of key signaling molecules and transcription factors, such as MAPKs, STATs, and NF-jB p65 subunit, which are involved in the production of proinflammatory cytokines by immune cells, and also directly affected transcription of proinflammatory genes. 43 Consistent with these observations, our results demonstrate that DIZE alleviated the ocular inflammation not only by reducing the amount of infiltrating CD45 þ inflammatory cells, but also by decreasing the retinal expression of the inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 91%
“…The study also showed that DIZE downregulated the phosphorylation of key signaling molecules and transcription factors, such as MAPKs, STATs, and NF-jB p65 subunit, which are involved in the production of proinflammatory cytokines by immune cells, and also directly affected transcription of proinflammatory genes. 43 Consistent with these observations, our results demonstrate that DIZE alleviated the ocular inflammation not only by reducing the amount of infiltrating CD45 þ inflammatory cells, but also by decreasing the retinal expression of the inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 91%
“…Most recently, it was shown DIZE, an activator of endogenous ACE2, remarkably suppressed LPS induced production of proinflammatory cytokines. DIZE downregulated the phosphorylation of key signaling molecules and transcription factors including MAPKs, STATs, and NF-κB p65 subunit, which are involved in the production of proinflammatory cytokines29.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of signal transducer and activator of transcription 3 (STAT3) in CD4 + T cells is essential for the development of EAU, and mice with conditional deletion of STAT3 are completely resistant to EAU28. On the other hand, ACE2 activator DIZE mediates anti-inflammatory properties by down-regulating phosphorylation of p38MAPK, extracellular signal-regulated kinase (ERK), and c-Jun N-terminal kinase (JNK), STAT3 and NF-κB p65 subunit in macrophages29. Over-expression of ACE2 significantly inhibits the development of early atherosclerotic lesions in a rabbit model by down-regulating the p38MAPK, ERK1/2 and STAT3 pathways30.…”
mentioning
confidence: 99%
“…Although inflammation is considered as a protective mechanism elicited by the host in answer to various aggressions such as microbial infections, excessive inflammation often causes extensive tissue damage and even systemic dysfunction (Kuriakose et al, 2013; Chen et al, 2015). ALI is characterized by obvious acute inflammation with elevated pro-inflammatory cytokines levels, and is a major cause of morbidity and mortality in critically ill patients (Wu et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%